The determinants of bank efficiency in Malaysian banking industry - Ainie, Azalli (2017)
It is noted that the study of bank efficiency and its determinants has become a focal point in the banking literature. Unexpected situation in the economy system such as the financial crisis is found to give a negative impact to the bank efficiency performance. In addition, the presence of foreign banks in the local banking system also affects the bank efficiency. For Islamic banks, the prohibited elements such as riba, gharar and maisir are the key for the increments of Islamic banks efficiency performance as compared to conventional banks. Hence, this study is aims to examine the impact of determinants of bank efficiency components; namely financial crisis, origins of bank ownership (foreign banks versus domestic banks) and types of bank (Islamic banks versus conventional banks); on three components of bank efficiency which are technical efficiency, pure technical efficiency and scale efficiency. This study covers 404 observations of commercial banks from the year 2004 to 2015. Thus, this study only analyzes one crisis which is the 2007-2008 U.S. financial crisis. This study employ the Data Envelopment Analysis (DEA) approach to find the bank efficiency followed by Tobit regression model to test the relationship between the financial crisis, origins of bank ownership (foreign banks versus domestic banks), types of bank (Islamic banks versus conventional banks) and bank efficiency. This study discovers that financial crisis has a significant and positive impact on bank efficiency (technical efficiency and pure technical efficiency). As for the origins of bank ownership, foreign banks with better skills, expertise and technology, outperformed the domestic banks in scale efficiency. In contrast, domestic banks perform better in technical and pure technical efficiencies as compared to their foreign counterparts. Finally, the findings highlight that Islamic banks are technically and scale efficient than conventional banks. Meanwhile conventional banks performed better in pure technical efficiency than their Islamic counterparts. Therefore, these findings provide some policy implications to the policy makers and the bank management in continuously assess the performance of Malaysian banks.